The Effect of Personal Description Board Game towards Students’ Speaking Skill at SMAN 2 Bangkinang Kota - Indah Nabila; Vitri Angraini Hardi; Lusi Marleni (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking is a productive skill that involves communicative performance. To be able to speak in English for Senior High School students are difficult. It is found that at SMAN 2 Bangkinang Kota. Students are struggling with clear pronunciation and appropriate vocabulary when describing objects due to limited use of learning media and reliance on textbooks, resulting in low English speaking skills at SMAN 2 Bangkinang Kota. The objective of the study is to find out the effect of personal description board game towards students’ speaking skill at tenth grade of SMAN 2 Bangkinang Kota. The researcher use a quasi-experimental design with a quantitative approach which uses the SPSS program to process data. The researcher chose two classes as the sample. The X-10 class, as the experimental class consists of 33 students and the X-9 class, as the control class, consists of 32 students. The instrument of this research is speaking test. In collecting data, the researcher used pre-test, treatment, and post-test. Technique of data analysis used normality test, homogeneity test and T-test. The result showed t-table score obtained = 1.66 and significant score was 0.000. Because the score of t calculation 4.711 > t-table 1.66 and significant score of 0.000 < α = 0.05, then Ho was rejected and Ha was accepted. This means that the post-test score of experimental class compared to that in the control class was different. In conclusion, Personal Description board game had effect on students speaking skill at tenth grade of SMAN 2 Bangkinang Kota